VARIASI JUMLAH ELEKTRODA DAN BESAR TEGANGAN DALAM MENURUNKAN KANDUNGAN COD DAN TSS LIMBAH CAIR TEKSTIL DENGAN METODE ELEKTROKOAGULASI - Achmad Chusnun Ni’am; Jenny Caroline; M . Haris Afandi (Al-Ard: Jurnal Teknik Lingkungan, 2017)
The quality of environment especially the water bodies need to be improved on the pollution load of the household wastewater, which in general still does not have a liquid waste treatment plant. Electrocoagulation used in this research because of the simple and efficient method. The aim of study to know the ability of electrocoagulation method for reducing the concentration of COD and TSS in the wastewater from household textile industry. The sample was taken from the residual wastewater of textile dye (sarung) with a liquid waste requirement of 36 liters. The data for the analysis is the initial and final parameters data were COD and TSS. The electrodes were used aluminum (Al) as an anode and iron (Fe) as a cathode. The research variations were used the number of electrodes and the voltage. The results showed that the treatment of 4 electrodes with 12volt voltage could reduce the COD concentration up to 76% and TSS up to 85% in household wastewater of household textile industry. Keywords: COD, electrocoagulation, liquid waste, TSS